Desperadas (Regal Entertainment, 2008)
A story of four beautiful half-sisters w/ different idiosyncrasies and issues on family and relationship, it portrays the Filipino woman's many trials and how she comes w/ life's unending ups and downs but in the end realizes that all she really needs is love.